Science and technology in Korea : - Jeon, Sang-woon (M.I.T. Press, 1974)
It might surprise Western scientists to learn that there were periods in Korean history when the level of scientific achievement was the highest in Asia. This is the proposition that Dr. Sang-woon Jeon sets forth in the first comprehensive and systematic survey of Korean science to appear in any Western language. Dr. Jeon points up Korea's unique contributions to the history of science and technology as well as the country's role as a bridge between Japanese and Chinese science and civilization. Much of his discussion of Korean science focuses on instruments which he describes in great detail in chapters on astronomy, metereology, physics and physical technology, and geography and cartography.Faced with the considerable difficulty of writing a history based on inadequate written records, Dr. Jeon has made use of available artifacts and other materials which have received little attention either in East Asia or the West. He has also summarized historical research in Korean science to the present and compiled an extensive bibliography.